Pendekatan Dialogis & Edukasi E-safety parenting Sebagai Upaya Mereduksi Kecanduan Gadget Anak dan Remaja di Desa Mubung, Kalimantan Barat - Anindita Imam Basri; Arif Aulia; Valsa Ayunda Tisya (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
In this disruptive era, internet and social media users in Indonesia are still showing an increasing trend until 2021. Teenagers are also among the most active internet users. Implicitly, excessive internet use will have a negative impact on adolescents' psychological and cognitive. Until now, many teenagers have been addicted to gadgets. This is experienced by teenagers in Desa Mubung, Kecamatan Hulu Gurung, Kapuas Hulu, Provinsi Kalimantan Barat, so it is very important to provide solutions to address the problems and needs of partners, namely: 1) Dialogic approach to parents in Mubung Village. 2) Socialization regarding e-safety parenting. 3) Training on how to use the e-safety parenting feature. or the target of the service, namely the parents of the children and youth of Desa Mubung. Based on the analysis of the partners' problems, community service activities generally aim to reduce the problem of gadget addiction and improve the quality of youth. The service method used is a dialogical approach, counseling, training, discussion, question and answer, and program evaluation through questionnaires. The results of the service show an increase in the percentage of knowledge and understanding of each indicator. In other words, the implementation of community service activities has succeeded in improving the quality of human resources in Desa Mubung, both parents and youth..